1988
DOI: 10.1007/bf00229392
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of liver cytochrome P-446 isolated from protein energy malnourished rats

Abstract: A liver cytochrome P-450 isozyme has been purified to homogeneity from protein-energy malnourished rats induced with beta-naphthoflavone (beta-NF). The purification steps included chromatography on DEAE-Sephadex-A-25, DEAE-cellulose (DE-53), hydroxylapatite (HA) and carboxymethyl-sephadex (CM) columns. The reduced carbon monoxide difference and absolute spectra showed a Soret peak at 446.5 nm. The wavelength maxima for the oxidized and reduced spectra were at 416 and 408 nm, respectively. Cytochrome P-446 appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
1988
1988

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…It was concluded that nutritional status drastically changes the levels of some P-450 isozymes, providing an explanation for the observed changes in aryl hydrocarbon hydroxylase activity. More recently, Gil et a f . (1988) have purified to homogeneity and characterized a cytochrome P-450 isozyme from protein-energy malnourished rats induced with (3-naphthoflavone.…”
Section: Introductionmentioning
confidence: 97%
“…It was concluded that nutritional status drastically changes the levels of some P-450 isozymes, providing an explanation for the observed changes in aryl hydrocarbon hydroxylase activity. More recently, Gil et a f . (1988) have purified to homogeneity and characterized a cytochrome P-450 isozyme from protein-energy malnourished rats induced with (3-naphthoflavone.…”
Section: Introductionmentioning
confidence: 97%